The Monastic Dimension of Identity Politics: Global Case Studies from the Premodern Period - Accardi, Dean; Accardi, Dean; Bevilacqua, Daniela; Eichman, Jennifer; Hoel, Nikolas O.; Jamroziak, Emilia; Jamroziak, Emilia; Maitra, Nabanjan; Papasidero, Marco; Papasidero, Marco; Steckel, Sita (Spirituality and Monasticism, East and West, 2024)
This volume comparatively explores how members of “monastic” communities, broadly understood, developed practical strategies for the construction of identity across a range of religious traditions in the greater regions of premodern Europe and Asia. In particular, it seeks to understand how the production, distribution, and reception of hagiographic material (written, visual, and performative) served as a tool for the implementation of “monastic” dynamics of legitimation. This is accomplished by pursuing and developing a two-fold approach. At an empirical level, the volume expands our scholarly understanding of the cross-cultural processes that characterize religious communities’ notions of identity. At a meta-level, it furthers a re-evaluation of our taxonomy as it challenges established notions of categories such as “monk/monastic” and “hagiography.”